Lingual nerve in relation to mandibular third molar region: a cadaveric study - Chalise, Usha; Kharbuja, Rabita; Dhungel, Shaligram; Bimb, Kushal (Journal of Chitwan Medical College, 2022)
Background: The lingual nerve is the terminal branch of the mandibular division of trigeminal nerve. The spatial relationship of lingual nerve to the mandibular alveolar crest varies widely. This variation can be among the gender, age, dental status and between the right and left side of the same sample. This study was aimed to determine the relationship of lingual nerve to mandibular third molar region. Methods: An observational study was carried out from January 2021 to December 2021.The study sample was 15 cadavers including both right and left sides. The lingual nerve was exposed by dissecting the infra temporal region following the standard procedures of Cunninghams Manual of Dissection. The diameter of the lingual nerve, vertical and horizontal distance were measured. The results of all these measurements were tabulated and mean standard deviation were calculated using SPSS version 16. Results: Out of 30 lingual nerves examined, the mean horizontal distance was 3.99 ± 0.96 mm, the mean vertical distance was 12.67 ± 1.76 mm while the diameter of the lingual nerve was 2.46 ± 0.54 mm. Conclusions: The lingual nerve always lies in close proximity of alveolar bone and surgeons operating in this region need to be aware during any surgical interventions or any procedures in this region. A thorough apprehension of the spatial location of the lingual nerve enable to lessen the lingual nerve injury.